Pelatihan Teknologi Informasi Untuk Meningkatkan Kompetensi Siswa Di SMAN 1 Sakra Timur - Deni Hanapi; Diki Setiawan Jodi; Baiq Andriska Candra Permana; Amri Muliawan Nur; Moh. Farid Wajdi (Universitas Hamzanwadi, 2025)
The use of information technology in education, especially in rural areas, is crucial for improving students' skills. This study aims to enhance the skills of SMAN 1 Sakra Timur students in operating Microsoft Office applications through intensive training focused on hands-on practice. The program lasts for 18 days, involving 15 students with a participatory method and step-by-step evaluation. The training material covers an introduction to basic to advanced features of Microsoft Word, Excel, and PowerPoint. Evaluation is carried out using pre-tests and post-tests, showing an increase in the average score from 45 to 85 percent. Students also provide positive feedback and appreciate the interactive approach used. The results of this training demonstrate that a practice-based approach is highly effective in improving the digital competencies of students at SMAN 1 Sakra Timur. This program is expected to inspire other schools to adopt similar training, enabling students to better face the challenges of the digital era and prepare for an increasingly competitive world of work and education.